Cardanol mercaptomaleic acid and preparation method thereof, cardanol-based toughened vinyl light-cured resin and preparation method and application of cardanol-based toughened vinyl light-cured resin
By introducing cashew phenol thiol maleic acid to improve chain modification of epoxy resin, the shortcomings of traditional epoxy resin in high toughness and antibacterial properties were solved, and cashew phenol-based toughening with excellent mechanical properties and rapid curing ability were prepared. Vinyl photocuring resin, suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202411229616.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-03
AI Technical Summary
Traditional epoxy resins are insufficient in some applications, especially in the need for high toughness, rapid curing or special environments (such as antibacterial and corrosion-resistant), existing vinyl ester resins have low curing activity and poor mechanical properties, and the surface It is easy to get sticky and difficult to meet industrial needs.
By introducing cashew phenol thiol maleic acid, the antibacterial action of its benzene ring structure complexed with metal ions and long side chain fat groups are introduced, and the functional group hydroxyl group is introduced through photoclick reaction, and the carboxylic acid structure is further obtained through esterification reaction, participating in the ring Oxygen ring opening, chain-enhanced modified epoxy resin, and prepare cashew phenol-based toughened vinyl photocuring resin.
Improve the tensile strength and toughness of the cured film, regulate the glass transition temperature, enhance the cross-link density and storage stability of the resin, achieve rapid and efficient curing, and has excellent antibacterial and corrosion resistance, suitable for 3D printing materials, UV coatings, adhesives, packaging materials or anticorrosion coatings.
Smart Images

Figure BDA0005025691290000021 
Figure BDA0005025691290000111 
Figure FDA0005025691280000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a cardanol mercaptomaleic acid and a preparation method thereof, a cardanol-based toughened vinyl photocurable resin and a preparation method and application thereof. Background Art
[0002] Epoxy resin is formed by the reaction of epoxy groups and compounds containing multifunctional groups. By forming a three-dimensional network structure, it gives the material high strength, high modulus and excellent heat resistance. As an important polymer material, epoxy resin is widely used in many industrial fields due to its excellent mechanical properties, chemical corrosion resistance, good electrical insulation and adhesion. However, the performance of traditional epoxy resin still needs to be improved in certain applications, such as those requiring high toughness, fast curing or special environments (such as antibacterial and corrosion resistance).
[0003] Vinyl ester resin is usually obtained by the ring-opening addition reaction of epoxy resin and monounsaturated carboxylic acid, and then dissolved in unsaturated active monomer. From the structural point of view, firstly, because the double bond involved in free radical curing is located at the end of the molecular chain segment, it has high curing activity and is easy to form a mold; secondly, the commonly used epoxy resin is a bisphenol A type structure, with more rigid benzene ring structures on the main chain, so its cured film has high tensile strength.
[0004] Currently, the chain extenders commonly used for vinyl ester resins are mostly difunctional, and the final resin obtained has a linear structure. This type of resin has low curing activity, is easily sticky on the surface, and has poor mechanical properties, so it needs to be modified. Summary of the invention
[0005] According to the first aspect of the present invention, there is provided a cardanol mercapto maleic acid, the structural formula of which is:
[0006]
[0007] According to a second aspect of the present invention, there is provided a method for preparing the above-mentioned cardanol mercaptomaleic acid, comprising the following steps:
[0008] Cardanol and mercaptoethanol are subjected to a photo-click reaction to obtain cardanol mercapto alcohol; and cardanol mercapto alcohol is subjected to an esterification reaction with maleic anhydride to obtain cardanol mercaptomaleic acid.
[0009] The present invention utilizes that cardanol contains a benzene ring, a phenol structure and a long side chain aliphatic group. The phenol structure can be complexed with metal ions to play an antibacterial role; the side chain double bond can be modified by a photoclick reaction, and a new functional group hydroxyl group can be introduced, so that a carboxylic acid structure can be further obtained by an esterification reaction, and the carboxylic acid structure can participate in the ring opening of epoxy, so that the epoxy resin can be chain-extended. In addition, the long side chain aliphatic group of cardanol can increase the toughness of the vinyl resin.
[0010] In some embodiments, the preparation method of cardanol mercaptomaleic acid comprises the following steps:
[0011] In parts by mass, 140-160 parts of cardanol, 80-90 parts of mercaptoethanol and 5-10 parts of photoinitiator are reacted under ultraviolet light for 3-7 hours to obtain cardanol mercapto alcohol; then 50-70 parts of cardanol mercapto alcohol and 80-90 parts of maleic anhydride are reacted at 50-120° C. for 18-30 hours to obtain cardanol mercaptomaleic acid.
[0012] In some embodiments, the photoinitiator is ITX photoinitiator (2-isopropylthioxanthone), 1173 photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), or TPO photoinitiator (diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide).
[0013] According to the third aspect of the present invention, there is provided a cardanol-based toughened vinyl photocurable resin, the raw material composition of which comprises, by weight: 120-160 parts of epoxy resin, 0.9-1.4 parts of catalyst, 0.03-0.06 parts of inhibitor, 45-63 parts of monounsaturated carboxylic acid containing olefinic bonds, 2-56 parts of cardanol mercaptomaleic acid, and 55-75 parts of active diluent.
[0014] In some embodiments, the epoxy resin is at least one of bisphenol A epoxy resin, bisphenol AD epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin.
[0015] In some embodiments, the catalyst is at least one of benzyltriethylammonium chloride, dibutyltin dilaurate, triethylamine, and triphenylphosphine.
[0016] In some embodiments, the polymerization inhibitor is at least one of hydroquinone, p-tert-butylcatechol, and catechol.
[0017] In some embodiments, the olefinically unsaturated monocarboxylic acid is at least one of acrylic acid, methacrylic acid, crotonic acid, and phenylacrylic acid.
[0018] In some embodiments, the reactive diluent is at least one of styrene, α-methylstyrene, methyl acrylate, isobornyl acrylate, tripropylene glycol diacrylate, and trimethylolpropane triacrylate.
[0019] According to a fourth aspect of the present invention, there is provided a method for preparing the above-mentioned cardanol-based toughened vinyl photocurable resin, comprising the following steps:
[0020] The epoxy resin is reacted with a monounsaturated carboxylic acid containing an olefinic bond under the action of a catalyst and an inhibitor, and then the remaining epoxy groups are completely reacted with cardanol mercapto maleic acid, and finally an active diluent is added and mixed evenly to obtain the product.
[0021] The present invention utilizes the cardanol mercapto maleic acid obtained by modifying cardanol with mercaptoethanol and maleic anhydride to carry out chain extension modification on epoxy resin to obtain a modified vinyl ester resin, and then the cardanol-based toughened vinyl photocurable resin is obtained by free radical curing of double bonds. Specifically, a difunctional cardanol mercapto maleic acid is first synthesized as a chain extender, and then the epoxy resin and the monobasic unsaturated carboxylic acid containing olefinic bonds are reacted for half-end blocking, and then the cardanol mercapto maleic acid is used for chain extension, and finally a reactive diluent is added for dilution to obtain the cardanol-based toughened vinyl photocurable resin. The present invention introduces the cardanol mercapto maleic acid containing a long carbon chain into the epoxy resin containing a large number of benzene ring structures, which can effectively improve the tensile strength and toughness of the cured film, and the glass transition temperature of the cured film can be adjusted regularly, the storage stability is good, the cross-linking density is high, and the curing method is efficient, convenient and green.
[0022] In some embodiments, the method for preparing the cardanol-based toughened vinyl photocurable resin comprises the following steps:
[0023] The epoxy resin, catalyst, polymerization inhibitor and olefinic monounsaturated carboxylic acid are reacted at 85-110°C for 2-5 hours until the acid value is less than 30 mg KOH / g, and then the cardanol mercapto maleic acid is added and the reaction is continued at 85-110°C for 2-5 hours until the acid value is less than 30 mg KOH / g, and then the reaction is cooled to below 80°C, and an active diluent is added and mixed uniformly to obtain the product.
[0024] According to a fifth aspect of the present invention, there is provided a use of the above-mentioned cardanol-based toughened vinyl photocurable resin in the preparation of 3D printing materials, UV coatings, adhesives, packaging materials or anti-corrosion coatings.
[0025] The beneficial effects of the present invention include:
[0026] (1) The present invention introduces a cardanol-based toughening agent cardanol mercapto maleic acid containing a long carbon chain into a petroleum-based epoxy resin, and combines a petroleum-based epoxy resin with high hardness and poor toughness with cardanol mercapto maleic acid with good toughness and low hardness through a ring-opening reaction of epoxy and carboxylic acid. Cardanol mercapto maleic acid has a difunctional structure, which can increase the crosslinking density of the resin, thereby increasing the toughness of the resin while maintaining a high hardness. With the different amounts of cardanol mercapto maleic acid, the glass transition temperature of the obtained cured film shows regular changes, thereby the glass transition temperature of the cured film can be regularly regulated. The cardanol-based toughened vinyl photocurable resin prepared by the present invention has a uniform appearance without stratification, a low viscosity, and is suitable for preparing 3D printing materials, UV coatings, adhesives, packaging materials or anti-corrosion coatings.
[0027] (2) The present invention combines cardanol with a vinyl resin and uses a photocuring technology to achieve rapid curing, thereby preparing a new resin material with excellent toughness, antibacterial properties, corrosion resistance and rapid curing ability. The cardanol-based toughened vinyl photocuring resin of the present invention not only effectively improves the mechanical properties, antibacterial properties and corrosion resistance of the cured film, but also makes full use of the advantages of photocuring technology such as rapidity, energy saving and controllability, providing the industry with a high-performance, environmentally friendly new material solution. At the same time, the introduction of cardanol also helps to reduce the cost of the resin and improve its competitiveness in the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is the reaction scheme of step (1) of Example 1 of the present invention.
[0029] Figure 2 This is the reaction scheme of step (2) of Example 1 of the present invention.
[0030] Figure 3 This is the reaction scheme of step (3) of Example 1 of the present invention.
[0031] Figure 4 It is the Fourier transform infrared spectrum of cardanol, cardanol mercapto alcohol and cardanol mercaptomaleic acid in Example 1 of the present invention.
[0032] Figure 5 It is the Fourier transform infrared spectra of the epoxy resin and the cardanol-based toughened vinyl photocurable resin of Example 1 of the present invention.
[0033] Figure 6 These are the electrochemical impedance diagrams of the resin coatings of Comparative Example 1, Example 1, Example 3, and Example 5. DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with specific examples, but the embodiments of the present invention are not limited thereto. The materials involved in the following examples can all be obtained from commercial channels.
[0035] Example 1
[0036] The preparation method of the cardanol-based toughened vinyl photocurable resin of this embodiment comprises the following steps:
[0037] (1) Add 150.0g of cardanol, 85.9g of mercaptoethanol, and 7.1g of 1173 photoinitiator to a 500mL round-bottom flask, stir magnetically, and irradiate under 365nm ultraviolet light for about 5h. When the double bond peak disappears completely by infrared observation, the reaction endpoint is reached. Then, add 300g of dichloromethane to the round-bottom flask to dissolve, transfer the solution to a separatory funnel, and wash with deionized water until the water layer is no longer turbid. Finally, the organic phase is evaporated at 45°C to remove the solvent to obtain light yellow transparent cardanol mercapto alcohol. The reaction route of this step is as follows: Figure 1 shown.
[0038] (2) In a 500 mL three-necked flask, 60.0 g of the cardanol mercapto alcohol obtained in step (1) and 82.4 g of maleic anhydride were added, and the mixture was stirred magnetically. The temperature was raised to 80° C. in a nitrogen environment and the mixture was kept warm for 24 h. The reaction product was tested by infrared observation and the reaction endpoint was reached when the carboxyl peak appeared. Ethyl acetate was added to the obtained reaction product to dissolve it, and the product was washed with deionized water. The ethyl acetate was then removed by rotary evaporation at 50° C. to obtain dark yellow transparent cardanol mercapto maleic acid. The reaction route of this step is as follows: Figure 2 shown.
[0039] (3) In a 500 mL round-bottom flask, add 145.28 g of bisphenol A epoxy resin E-44 (molecular weight 454), 59.38 g of acrylic acid, 0.0418 g of inhibitor hydroquinone, and 1.0462 g of catalyst benzyltriethylammonium chloride. Heat to 90°C and react for about 3.5 hours until the acid value is less than 30 mgKOH / g. Then add 4.58 g of cardanol mercaptomaleic acid obtained in step (2) and react at 90°C for about 3.5 hours until the acid value is less than 30 mgKOH / g. Then cool to below 80°C, add 62.77 g of styrene, mix well, and obtain a light yellow transparent cardanol-based toughened vinyl photocurable resin. The reaction route of this step is as follows: Figure 3 shown.
[0040] The Fourier transform infrared spectra of cardanol, cardanol mercapto alcohol and cardanol mercapto maleic acid in this example are as follows: Figure 4 As shown in the figure, the Fourier transform infrared spectra of epoxy resin and cardanol-based toughened vinyl photocurable resin are as follows Figure 5 shown.
[0041] from Figure 4 By comparison, it can be seen that the raw material is cardanol (denoted as CA), the product of step (1) is cardanol mercapto alcohol (denoted as CAM), and the product of step (2) is cardanol mercapto maleic acid (denoted as CAMM). Specifically:
[0042] In the FTIR spectrum of CA, 3010 cm -1 Corresponding to the characteristic stretching vibration of CH of C=CH on the side chain; 2928cm -1 and 2855cm -1 Corresponding to the asymmetric stretching of methylene and methyl groups in long aliphatic chains; and 3600cm -1 Up to 3300cm -1 The long peak is the stretching vibration of OH on the benzene ring, that is, the characteristic peak of phenol-OH. When CA reacts with mercaptoethanol by photo-click reaction, 3010cm -1 The peak of 1050cm-1 disappeared, indicating that mercaptoethanol reacted completely with the double bond of the side chain of cardanol. -1 The peak at 1724 cm -1 A new signal peak appears, which is the carbonyl stretching vibration of the ester group, 1220cm -1 and 1404cm -1 The two new peaks at are the stretching vibrations of the ester bond CO, indicating that maleic anhydride and CAM are successfully grafted together. Therefore, the FT-IR results show that the product of step (2) is CAMM.
[0043] from Figure 5 By comparison, it can be seen that the raw material is epoxy resin (denoted as E44) and the product is cardanol-based toughened vinyl light-curing resin (denoted as VER). Specifically:
[0044] Seen in E44 at 915cm -1 The characteristic peak that appears nearby is the epoxy vibration peak, 1607cm -1 is the stretching vibration of C=C on the benzene ring, 831cm -1 It is the absorption peak of the opposite substitution vibration on the benzene ring. When E44 undergoes a series of ring-opening and end-capping reactions, 915cm -1 The characteristic peak of epoxy group disappeared, indicating that the epoxy group reacted with carboxylic acid to complete the ring opening, 1724cm -1 The peak of C=O stretching vibration on the unsaturated monoester bond is shown in Figure 1. Therefore, the FT-IR results show that the product is a cardanol-based toughened vinyl photocurable resin.
[0045] Example 2
[0046] The preparation method of the cardanol-based toughened vinyl photocurable resin of this embodiment comprises the following steps:
[0047] (1) 150.0 g of cardanol, 85.9 g of mercaptoethanol, and 7.1 g of 1173 photoinitiator were added to a 500 mL round-bottom flask, and the mixture was irradiated under 365 nm ultraviolet light for about 5 h. The reaction endpoint was reached when the double bond peak disappeared completely by infrared observation. Then 300 g of dichloromethane was added to the round-bottom flask to dissolve it, and the solution was transferred to a separatory funnel and washed with deionized water until the water layer was no longer turbid. Finally, the organic phase was evaporated at 45 ° C to remove the solvent to obtain light yellow transparent cardanol mercapto alcohol.
[0048] (2) 60.0 g of the cardanol mercapto alcohol obtained in step (1) and 82.4 g of maleic anhydride were added to a 500 mL three-necked flask, and the mixture was stirred magnetically. The temperature was raised to 80° C. in a nitrogen environment and the mixture was kept warm for 24 h. The reaction product was tested by infrared and the carboxyl peak appeared, indicating that the reaction endpoint was reached. Ethyl acetate was added to the obtained reaction product to dissolve it, and the product was washed with deionized water. The ethyl acetate was then removed by rotary evaporation at 50° C. to obtain dark yellow transparent cardanol mercapto maleic acid.
[0049] (3) In a 500 mL round-bottom flask, 145.28 g of bisphenol A epoxy resin E-44 (molecular weight 454), 56.49 g of acrylic acid, 0.0436 g of inhibitor hydroquinone, and 1.0890 g of catalyst benzyltriethylammonium chloride were added, and the temperature was raised to 90° C. to react for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then 16.0247 g of the cardanol mercapto maleic acid obtained in step (2) was added, and the reaction was carried out at 90° C. for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then the mixture was cooled to below 80° C., 65.34 g of styrene was added, and the mixture was mixed evenly to obtain a light yellow transparent cardanol-based toughened vinyl photocurable resin.
[0050] The cardanol mercapto alcohol, cardanol mercapto maleic acid, and cardanol-based toughened vinyl photocurable resin obtained in this example were tested by Fourier transform infrared spectroscopy. The characteristic peaks of the test results were basically consistent with those in Example 1, and will not be repeated here to save space.
[0051] Example 3
[0052] The preparation method of the cardanol-based toughened vinyl photocurable resin of this embodiment comprises the following steps:
[0053] (1) 150.0 g of cardanol, 85.9 g of mercaptoethanol, and 7.1 g of 1173 photoinitiator were added to a 500 mL round-bottom flask, and the mixture was irradiated under 365 nm ultraviolet light for about 5 h. The reaction endpoint was reached when the double bond peak disappeared completely by infrared observation. Then 300 g of dichloromethane was added to the round-bottom flask to dissolve it, and the solution was transferred to a separatory funnel and washed with deionized water until the water layer was no longer turbid. Finally, the organic phase was evaporated at 45 ° C to remove the solvent to obtain light yellow transparent cardanol mercapto alcohol.
[0054] (2) 60.0 g of the cardanol mercapto alcohol obtained in step (1) and 82.4 g of maleic anhydride were added to a 500 mL three-necked flask, and the mixture was stirred magnetically. The temperature was raised to 80° C. in a nitrogen environment and the mixture was kept warm for 24 h. The reaction product was tested by infrared and the carboxyl peak appeared, indicating that the reaction endpoint was reached. Ethyl acetate was added to the obtained reaction product to dissolve it, and the product was washed with deionized water. The ethyl acetate was then removed by rotary evaporation at 50° C. to obtain dark yellow transparent cardanol mercapto maleic acid.
[0055] (3) In a 500 mL round-bottom flask, 145.28 g of bisphenol A epoxy resin E-44 (molecular weight 454), 53.62 g of acrylic acid, 0.0436 g of inhibitor hydroquinone, and 1.0890 g of catalyst benzyltriethylammonium chloride were added, and the temperature was raised to 90° C. to react for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then 27.4709 g of the cardanol mercapto maleic acid prepared in step (2) was added, and the reaction was carried out at 90° C. for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then the mixture was cooled to below 80° C., 65.3406 g of styrene was added, and the mixture was mixed evenly to obtain a light yellow transparent cardanol-based toughened vinyl photocurable resin.
[0056] The cardanol mercapto alcohol, cardanol mercapto maleic acid, and cardanol-based toughened vinyl photocurable resin obtained in this example were tested by Fourier transform infrared spectroscopy. The characteristic peaks of the test results were basically consistent with those in Example 1, and will not be repeated here to save space.
[0057] Example 4
[0058] The preparation method of the cardanol-based toughened vinyl photocurable resin of this embodiment comprises the following steps:
[0059] (1) 150.0 g of cardanol, 85.9 g of mercaptoethanol, and 7.1 g of 1173 photoinitiator were added to a 500 mL round-bottom flask, and the mixture was irradiated under 365 nm ultraviolet light for about 5 h. The reaction endpoint was reached when the double bond peak disappeared completely by infrared observation. Then 300 g of dichloromethane was added to the round-bottom flask to dissolve it, and the solution was transferred to a separatory funnel and washed with deionized water until the water layer was no longer turbid. Finally, the organic phase was evaporated at 45 ° C to remove the solvent to obtain light yellow transparent cardanol mercapto alcohol.
[0060] (2) 60.0 g of the cardanol mercapto alcohol obtained in step (1) and 82.4 g of maleic anhydride were added to a 500 mL three-necked flask, and the mixture was stirred magnetically. The temperature was raised to 80° C. in a nitrogen environment and the mixture was kept warm for 24 h. The reaction product was tested by infrared and the carboxyl peak appeared, indicating that the reaction endpoint was reached. Ethyl acetate was added to the obtained reaction product to dissolve it, and the product was washed with deionized water. The ethyl acetate was then removed by rotary evaporation at 50° C. to obtain dark yellow transparent cardanol mercapto maleic acid.
[0061] (3) In a 500 mL round-bottom flask, 145.28 g of bisphenol A epoxy resin E-44 (molecular weight 454), 50.73 g of acrylic acid, 0.0470 g of inhibitor hydroquinone, and 1.1746 g of catalyst benzyltriethylammonium chloride were added, and the temperature was raised to 90° C. to react for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then 38.92 g of the cardanol mercapto maleic acid obtained in step (2) was added, and the reaction was carried out at 90° C. for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then the mixture was cooled to below 80° C., 70.48 g of styrene was added, and the mixture was mixed evenly to obtain a light yellow transparent cardanol-based toughened vinyl photocurable resin.
[0062] The cardanol mercapto alcohol, cardanol mercapto maleic acid, and cardanol-based toughened vinyl photocurable resin obtained in this example were tested by Fourier transform infrared spectroscopy. The characteristic peaks of the test results were basically consistent with those in Example 1, and will not be repeated here to save space.
[0063] Example 5
[0064] The preparation method of the cardanol-based toughened vinyl photocurable resin of this embodiment comprises the following steps:
[0065] (1) 150.0 g of cardanol, 85.9 g of mercaptoethanol, and 7.1 g of 1173 photoinitiator were added to a 500 mL round-bottom flask, and the mixture was irradiated under 365 nm ultraviolet light for about 5 h. The reaction endpoint was reached when the double bond peak disappeared completely by infrared observation. Then 300 g of dichloromethane was added to the round-bottom flask to dissolve it, and the solution was transferred to a separatory funnel and washed with deionized water until the water layer was no longer turbid. Finally, the organic phase was evaporated at 45 ° C to remove the solvent to obtain light yellow transparent cardanol mercapto alcohol.
[0066] (2) 60.0 g of the cardanol mercapto alcohol obtained in step (1) and 82.4 g of maleic anhydride were added to a 500 mL three-necked flask, and the mixture was stirred magnetically. The temperature was raised to 80° C. in a nitrogen environment and the mixture was kept warm for 24 h. The reaction product was tested by infrared and the carboxyl peak appeared, indicating that the reaction endpoint was reached. Ethyl acetate was added to the obtained reaction product to dissolve it, and the product was washed with deionized water. The ethyl acetate was then removed by rotary evaporation at 50° C. to obtain dark yellow transparent cardanol mercapto maleic acid.
[0067] (3) In a 500 mL round-bottom flask, 145.28 g of bisphenol A epoxy resin E-44 (molecular weight 454), 46.70 g of acrylic acid, 0.0494 g of inhibitor hydroquinone, and 1.2346 g of catalyst benzyltriethylammonium chloride were added, and the temperature was raised to 90° C. to react for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then 54.9417 g of the cardanol mercapto maleic acid obtained in step (2) was added, and the reaction was carried out at 90° C. for about 3.5 hours until the acid value was less than 30 mgKOH / g. Then the mixture was cooled to below 80° C., 74.08 g of styrene was added, and the mixture was mixed evenly to obtain a light yellow transparent cardanol-based toughened vinyl photocurable resin.
[0068] The cardanol mercapto alcohol, cardanol mercapto maleic acid, and cardanol-based toughened vinyl photocurable resin obtained in this example were tested by Fourier transform infrared spectroscopy. The characteristic peaks of the test results were basically consistent with those in Example 1, and will not be repeated here to save space.
[0069] Comparative Example 1
[0070] The preparation method of the modified vinyl ester resin of this comparative example comprises the following steps:
[0071] In a 500 mL round-bottom flask, 145.28 g of bisphenol A epoxy resin E-44 (molecular weight 454), 53.62 g of acrylic acid, 0.0398 g of inhibitor hydroquinone, and 0.9945 g of catalyst benzyltriethylammonium chloride were added, and the temperature was raised to 90° C. to react until the acid value was less than 30 mgKOH / g. Then, the mixture was cooled to below 80° C., 59.67 g of styrene was added, and the mixture was mixed evenly to obtain a modified vinyl ester resin.
[0072] In order to detect the comprehensive mechanical properties, thermal stability, antibacterial properties and corrosion resistance of the cardanol-based toughened vinyl photocurable resin prepared by the present invention, the cardanol-based toughened vinyl photocurable resin prepared in Examples 1-5 and the modified vinyl ester resin prepared in Comparative Example 1 were made into cured films, and then the obtained cured films were subjected to plastic tensile properties test, dynamic thermal mechanical properties test, thermogravimetric test, antibacterial test and electrochemical test.
[0073] 1. Preparation of cured film
[0074] The cardanol-based toughened vinyl photocurable resin prepared in Examples 1-5 and the modified vinyl ester resin prepared in Comparative Example 1 were respectively mixed evenly with 1173 photoinitiator in an amount of 5wt% of the total mass of the resin, and irradiated with ultraviolet light for 3 minutes to obtain the obtained product.
[0075] 2. Carry out plastic tensile properties test, dynamic thermomechanical properties test, thermogravimetric test, antibacterial test and electrochemical test on the prepared cured film
[0076] (1) Plastic tensile properties test: The tensile test was performed using Shimadzu's AGS-X 1kN universal tester. The dumbbell-shaped sample specifications were based on GB / T 1040.2-2006. The crosshead speed was 1 mm min -1 Young's modulus is the ratio of tensile strength to elongation at break. For accuracy, each sample was measured three times and the average value was taken.
[0077] (2) Dynamic thermomechanical properties test: The test was performed using a Netzsch DMA 242E dynamic thermomechanical instrument, with the tensile mode selected and the oscillation frequency set to 1 Hz. During the test, the sample was first cooled to -80°C with liquid nitrogen and kept at -50°C for 3 minutes, then heated at 5°C / min. -1 The sample was heated to 180°C at a speed of 100°C. The sample size was 32mm×5mm×3mm (length×width×thickness). The glass transition temperature (Tg) of the cured film corresponds to the peak temperature on the tanδ vs. temperature curve. For accuracy, each sample was measured three times and the average value was taken.
[0078] (3) Thermogravimetric test method: Thermogravimetric analysis was performed using a Netzsch STA 449C thermal analyzer. The temperature range required for the thermogravimetric test of the sample was set to 35-650°C, and the heating rate was 10°C min -1 During the test, the nitrogen environment was maintained and the nitrogen introduction rate was 60 mL min -1 For the sake of accuracy, three measurements were performed for each sample and the average value was taken.
[0079] (4) Antibacterial test method: 1 g of the resin before curing and 1 g of the cured film after curing were added to 9 mL of liquid culture medium (consisting of 0.1 g of peptone, 0.05 g of beef extract, 0.05 g of sodium chloride, and 10 mL of distilled water), and 1 mL of bacterial solution (10 7 CUF / mL), and then the obtained suspension was sealed in a test tube and placed in a constant temperature incubator for shaking culture for 24 hours. The suspension without adding resin or cured film sample (containing 9mL liquid culture medium and 1mL bacterial solution) was used as a blank control. The OD value of the suspension at 600nm was measured using a UV-5500PC ultraviolet spectrophotometer. The survival rate of the strain was calculated according to the following formula: Survival rate (%) = OD x / OD0, where OD x is the OD value of the sample containing resin or cured film; OD0 is the OD value of the blank control. For the sake of accuracy, each sample was measured three times and the average value was taken.
[0080] (5) Electrochemical test method: The corrosion resistance of the metal sheet coated with the resin coating after being immersed in a 3.5 wt % NaCl aqueous solution was evaluated using the EIS technique in a CHI660E electrochemical workstation. 2 The sample was used as the working electrode, and the saturated Ag / AgCl electrode was used as the reference electrode with an area of 2.5 cm 2 A platinum plate was used as the counter electrode to establish a three-electrode system. The working electrode was immersed in the corrosive medium for 1 hour before the test to ensure that the working electrode had a stable open circuit potential (OCP) value. EIS measurements were performed under a stable open circuit potential, with a frequency range of 100KHz to 0.01Hz and a voltage of 20mV sinusoidal amplitude. For accuracy, at least three splines were prepared for each sample.
[0081] 3. Test results
[0082] (1) Comprehensive mechanical properties test results
[0083] The comprehensive mechanical properties test results of the cured film are shown in Table 1.
[0084] Table 1 Comprehensive mechanical properties test results of cured films
[0085] Tensile strength(MPa) Elongation at break (%) Tg(℃) Example 1 76.73 10.74 95.9 Example 2 77.79 11.57 89.4 Example 3 76.53 15.25 87.2 Example 4 76.70 9.32 82.8 Example 5 61.60 7.59 81.6 Comparative Example 1 57.44 5.23 96.5
[0086] As can be seen from Table 1, the cured film prepared by the cardanol-based toughened vinyl photocurable resin of Examples 1-5 of the present invention has a certain improvement in tensile properties and a decrease in glass transition temperature relative to the cured film prepared by the vinyl ester resin modified by cardanol mercapto maleic acid without adding cardanol mercapto maleic acid in Comparative Example 1. The tensile strength and elongation at break of the cured film prepared by the resin of Examples 1-5 of the present invention have a certain decrease after reaching the peak value, and the addition amount of cardanol mercapto maleic acid corresponding to the peak value is about 11% of the mass of E-44. The reason may be that the entanglement of the long carbon chain and the polymer chain and the rigid ring structure of the cardanol mercapto maleic acid improve the mechanical properties of the cured film, but when the cardanol mercapto maleic acid is continued to be added, the long carbon chain introduced is too much, which will cause a certain degree of decrease in the mechanical properties of the cured film. With the difference in the amount of cardanol mercapto maleic acid, the glass transition temperature of the obtained cured film shows regular changes, and the glass transition temperature of the cured film can be regularly regulated.
[0087] (2) Thermal stability test results
[0088] The thermal stability test results of the cured films are shown in Table 2.
[0089] Table 2 Thermal stability test results of cured films
[0090] <![CDATA[T 10% (℃)]]> <![CDATA[T 50% (℃)]]> Residual carbon rate (%) Example 1 343.07 422.57 6.482 Example 2 303.50 413.50 6.143 Example 3 303.11 419.74 4.539 Example 4 306.22 416.72 6.805 Example 5 300.68 413.68 5.542 Comparative Example 1 383.97 428.47 8.855
[0091] As can be seen from Table 2, with the addition of cardanol mercapto maleic acid, although a long bio-based carbon chain was introduced, the thermal stability of the resin did not decrease significantly due to the increase in cross-linking density, and the T 10% All are higher than 300℃, indicating that the resin has good thermal stability.
[0092] (3) Antibacterial performance test results
[0093] The test results of the antibacterial properties of the resin before and after photocuring are shown in Table 3.
[0094] Table 3 Antibacterial performance test results of resin before and after photocuring
[0095]
[0096] As can be seen from Table 3, the cardanol-based toughened vinyl light-cured resin of the present invention can significantly reduce the survival rate of Escherichia coli and the survival rate of Staphylococcus aureus before and after curing, relative to the vinyl ester resin modified by cardanol mercapto maleic acid without addition, and as the addition amount of cardanol mercapto maleic acid increases, the survival rate of Escherichia coli and the survival rate of Staphylococcus aureus are further reduced. The reason may be that with the addition of cardanol mercapto maleic acid, the hydrogen atoms in its phenolic hydroxyl group can form hydrogen bonds with the phosphate group, carbonyl group, etc. on the microbial cell membrane, and the interaction of this hydrogen bond can limit the free movement of cell membrane molecules, resulting in the colloidization of the cell membrane. This colloidization phenomenon can further affect the permeability and stability of the cell membrane, thereby enhancing the antibacterial effect of the phenolic hydroxyl group.
[0097] The reason for the difference in antibacterial properties of cardanol-based toughened vinyl light-curing resin before and after curing may be that during the curing process of the resin, the phenolic hydroxyl group of cardanol mercapto maleic acid, as part of the curing agent, undergoes an addition reaction with the oxygen atom in the epoxy group of the resin to form a new chemical bond, thereby promoting the cross-linking and curing of the epoxy resin. Since there are fewer phenolic hydroxyl groups in cardanol mercapto maleic acid that can form hydrogen bonds with the phosphate group, carbonyl group, etc. on the microbial cell membrane after the resin is cured, the antibacterial properties of the resin after curing decrease to a certain extent.
[0098] (4) Electrochemical test results
[0099] The electrochemical impedance diagrams of the resin coatings of Comparative Example 1, Example 1, Example 3, and Example 5 are as follows: Figure 6 shown.
[0100] from Figure 6 It can be seen that at the initial stage of immersion, the Bode impedance curves of the resin coatings of Comparative Example 1, Example 1, Example 3, and Example 5 all show diagonal lines in a wide frequency range, and the |Z| 0.01Hz The value difference is small, both close to 10 11 Ω·cm 2 , showing excellent anti-corrosion performance. The Bode impedance curve of the resin coating of comparative example 1 shows that the resin coating of comparative example 1 shows lower |Z| in the middle of immersion. 0.01Hz Value, with the extension of immersion time, the resin coating of comparative example 1 has |Z| 0.01Hz The value quickly increased from 6.89×10 10 Ω·cm 2 Down to 7.24×10 7 Ω·cm 2 , which is nearly 3 orders of magnitude lower than the value at the initial immersion, and still does not reach a steady state even after a long immersion time, |Z| 0.01HzThe value is still decreasing, which means that the corrosion resistance of the resin coating of Comparative Example 1 has been decreasing. After 120 days of immersion, |Z| 0.01Hz The value is 3.09×10 5 Ω·cm 2 .
[0101] From the Bode impedance curves of the resin coatings of Example 1, Example 3, and Example 5, it can be seen that the resin coatings of Example 1, Example 3, and Example 5 to which cardanol mercaptomaleic acid is added, |Z| 0.01Hz The value changes tend to be stable. After immersion for 180 days, the |Z| of the resin coatings of Example 1, Example 3, and Example 5 0.01Hz The values are as high as 5.92×10 8 Ω·cm 2 , 6.42×10 9 Ω·cm 2 , 3.34×10 9 Ω·cm 2 , which only decreases by about 2 orders of magnitude compared to the |Z| of the resin coating of Comparative Example 1 after 120 days. 0.01Hz The value is about 5 orders of magnitude higher, indicating that the addition of cardanol mercaptomaleic acid improves the corrosion resistance of the resin coating.
[0102] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. Cardanol mercapto maleic acid, characterized in that Its structural formula is:
2. The method for preparing the cardanol mercaptomaleic acid according to claim 1, characterized in that: The steps include: Cardanol and mercaptoethanol are subjected to a photo-click reaction to obtain cardanol mercapto alcohol; and cardanol mercapto alcohol is subjected to an esterification reaction with maleic anhydride to obtain cardanol mercaptomaleic acid.
3. The method for preparing cardanol mercaptomaleic acid according to claim 2, characterized in that: The steps include: In parts by mass, 140-160 parts of cardanol, 80-90 parts of mercaptoethanol and 5-10 parts of photoinitiator are reacted under ultraviolet light for 3-7 hours to obtain cardanol mercapto alcohol; then 50-70 parts of cardanol mercapto alcohol and 80-90 parts of maleic anhydride are reacted at 50-120° C. for 18-30 hours to obtain cardanol mercaptomaleic acid.
4. The method for preparing cardanol mercaptomaleic acid according to claim 3, characterized in that: The photoinitiator is an ITX photoinitiator, a 1173 photoinitiator or a TPO photoinitiator.
5. Cardanol-based toughened vinyl photocurable resin, characterized in that: The raw material composition comprises, by weight: 120-160 parts of epoxy resin, 0.9-1.4 parts of catalyst, 0.03-0.06 parts of polymerization inhibitor, 45-63 parts of monounsaturated carboxylic acid containing olefinic bond, 2-56 parts of cardanol mercaptomaleic acid according to claim 1, and 55-75 parts of active diluent.
6. The cardanol-based toughened vinyl photocurable resin according to claim 5, characterized in that: The epoxy resin is at least one of bisphenol A epoxy resin, bisphenol AD epoxy resin, bisphenol F epoxy resin, and bisphenol S epoxy resin; The catalyst is at least one of benzyltriethylammonium chloride, dibutyltin dilaurate, triethylamine and triphenylphosphine; The polymerization inhibitor is at least one of hydroquinone, p-tert-butylcatechol and catechol.
7. The cardanol-based toughened vinyl photocurable resin according to claim 5 or 6, characterized in that: The olefinically unsaturated carboxylic acid is at least one of acrylic acid, methacrylic acid, crotonic acid, and phenylacrylic acid; The active diluent is at least one of styrene, α-methylstyrene, methyl acrylate, isobornyl acrylate, tripropylene glycol diacrylate, and trimethylolpropane triacrylate.
8. The method for preparing the cardanol-based toughened vinyl photocurable resin according to any one of claims 5 to 7, characterized in that: The steps include: The epoxy resin is reacted with a monounsaturated carboxylic acid containing an olefinic bond under the action of a catalyst and an inhibitor, and then the remaining epoxy groups are completely reacted with cardanol mercapto maleic acid, and finally an active diluent is added and mixed evenly to obtain the product.
9. The method for preparing the cardanol-based toughened vinyl photocurable resin according to claim 8, characterized in that: The steps include: The epoxy resin, catalyst, polymerization inhibitor and olefinic monounsaturated carboxylic acid are reacted at 85-110°C for 2-5 hours until the acid value is less than 30 mg KOH / g, and then the cardanol mercapto maleic acid is added and the reaction is continued at 85-110°C for 2-5 hours until the acid value is less than 30 mg KOH / g, and then the reaction is cooled to below 80°C, and an active diluent is added and mixed uniformly to obtain the product.
10. Use of the cardanol-based toughened vinyl photocurable resin according to any one of claims 5 to 7 in the preparation of 3D printing materials, UV coatings, adhesives, packaging materials or anti-corrosion coatings.
Citation Information
Patent Citations
Plant oil based thiol self-curing resin and preparation method and application thereof
CN108129589A
Multifunctional cardanol-based UV curing reactive diluent as well as preparation method and application thereof
CN111019418A
Cardanol polyoxyethylene maleic anhydride ester and preparation method thereof, and solid polycarboxylic acid slump retaining agent and preparation method thereof
CN111362613A
Eleostearic acid maleic anhydride modified vinyl ester resin as well as preparation method and application thereof
CN113637146A